Feminism and modern Islamic politics: the fact and the fallacy - Muhibbu-Din, Mahmudat Olawunmi (Penerbit Universiti Kebangsaan Malaysia, 2019)
Islam is perceived as a religion that relegates women in different spheres of life. This informs the Islamic feminists’ criticism of Islam as against gender equality. This study critically appraises the factors responsible for the exclusion of women in modern politics, explores the Islamic textual position on women’s roles in society; investigates the level of women political participation in states that have declared Islam as the state religion as compared with those that have not declared Islam. Methodology is comparative and content analysed. The findings show that gender inequality in political participation is a global phenomenon. Gender mainstreaming in some states that have declared Islam as the state religion is far ahead of some advanced democracies. Barriers to women’s political participation vary from socioeconomic to institutional. This paper stresses the role of women as political equals of men, yet their primary role as mothers, wives and daughters cannot be undermined.